Pengaruh Pendidikan Kesehatan tentang Skin Personal Hygiene Management terhadap Tindakan Perawatan Diri pada Narapidana Penderita Skabies di Lembaga Pemasyarakatan Klas II-A Jember (The Influence of Health Education about Skin Personal Hygiene Management - Devy Meylina Christy; Rondhianto Rondhianto; Murtaqib Murtaqib (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Scabies is a skin disease that can transmited to another person who live together in some place for a long time and cause pruritus, skin eruption, and scars. Skin Personal Hygiene Management can facilitate the knowledge, skill and ability of the patients to take care and prevent scabies infection. The objetive of the research was to analyze the influence of Health Education about Skin Personal Hygiene Management to the self care actions on prisoners with scabies. The method of the research was quasi experimental study with post test only with control group design. The sample of the research used total sampling with 22 prisoners with scabies respondent divided into 2 groups, experiment group dan control group which 11 respondent each group. Data were analyzed by using Independent T-test with 95% of Cl. The result showed that p value of Independent t-test was 0,000 (p < α; α = 0,05). The conclusion of this research is there was an influence of health education about Skin Personal Hygiene Management to self care actions on prisoners with scabies in Correctional Institution Class II-A Jember. Self care actions on experimental group was categorized 100% good, meanwhile on control group 90,9% categorized quite good. It is suggested that nurses can provide Skin Personal Hygiene Management to increase self care actions which can prevent scabies infection and using Skin Personal Hygiene Management as health education program. Keywords: scabies, self care action, health education, skin personal hygiene management